THE HOLISTIC CONCEPT IN THE STUDY OF CASES REQUIRING IMPLANTS - Tibeică Andreea; Siminiuc Petruta - Iuliana; Bolat Maria; Scurtu Mihaela; Curcă Răzvan; Norina Forna (Romanian Dental Association for Education, 2022)
This article aims to analyze different perspectives on addressing the situations of patients requiring oral rehabilitation with the help of dental implants, taking into account the holistic concept of identifying patients' needs and multidisciplinary factors. Thus, we will follow the principle of bone growth, for young adolescent patients, the principles of bacterial biofilm, periodontal disease, systemic diseases, lack of space, loss of alveolar bone, congenital diseases.